The pre-Linnaean herbarium of Paolo Boccone (1633–1704) kept in Leiden (the Netherlands) and its connections with the imprinted one in Paris - Costa, R. M. S.; van Andel, T.; Pavone, P.; Pulvirenti, S. (Plant biosystems, 2018)
The subject of this paper is the study of the pre-Linnaean herbarium of Paolo Boccone (1633-1704) which is kept in Leiden (the Netherlands) and its connections with two works of the same author: the imprinted herbarium kept in Paris in the Bibliothèques Interuniversitaires de Médecine and the printed volume "Icones et Descriptiones" of 1674. By means of the comparative analysis of the three works we have verified the existence of numerous similarities (even a complete overlap) between the samples of the Leiden herbarium (some with visible traces of ink), the imprints of the Paris herbarium and the figures of "Icones et Descriptiones". The drawings to be found in this work, thanks to the realistic fidelity that distinguishes them, have been used by various authors until quite recent times for the description of new taxa. This shows the importance and the usefulness of the herbarium in question for the processes of typification. The taxonomic identification of the specimens (121 angiosperms and 1 alga) allowed us to designate the lectotype and the epitype of Daucus gingidium subsp. polygamus (Gouan) Onno and of Daucus carota subsp. commutatus (Paol.) Thell.